Exploring travelers' decision-making styles. Issue 1 (8th January 2018) - Atadil, Hilmi A.; Sirakaya-Turk, Ercan; Meng, Fang; Decrop, Alain
Abstract : Purpose: The purpose of this study is to profile market segments using travelers' decision-making styles (DMS) as segmentation bases and to identify similarities and differences between traveler segments regarding a series of psychographic and attitudinal characteristics. Design/methodology/approach: Data are gathered from a sample of 426 travelers in Dubai and Shanghai via self-reported surveys. Analyses included factor, k-means cluster, discriminant and MANOVA. Findings: Study findings reveal significant differences among the rational, adaptive and daydreamer decision-makers' segments in their behavioral and attitudinal characteristics with respect to tourism involvement and destination images. Practical implications: Findings provide important practical implications for generating effective marketing and positioning strategies based on the identified attitudinal characteristics of the traveler segments for destination marketing organizations. Originality/value: A stream of recent tourism studies shows a strong relationship between tourism involvement and destination images, yet very little research has tackled the issue of how these critical variables can be affected by individuals' decision-making styles. This study explores and tests the relationships among DMS, tourism involvement and destination image using a factor-cluster approach.